Unsur Supranatural dalam Teks Lamut “Kerajaan Palinggam” - Irni Cahyani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Supernatural is above natural things, where supernatural is more aimed at the natural phenomenon and is debating culture/world. While the lamut is oral literature performed by a single player (palanutan). The only player brings a particular story through the speech which in certain parts of his speech accompanied by a wasp of tarbanglamut. In this study, researchers examined the supernatural element in the text of the lamut